Occupational therapy for people with learning disabilities : a practical guide - Goodman, Jane, 1942-; Hurst, Jenni; Locke, Christine; ScienceDirect eBooks (Edinburgh ; New York : Churchill Livingstone, 2009)
This book is aimed primarily at occupational therapy undergraduate students, but will be of use to new practitioners working in the field of learning disability and other students studying topics related to learning disabilities. It meets perceived learning needs in line with theory and practice outcomes and provides an understanding of the current issues in health and social care for people with a learning disability. It provides a basis for further learning and the depth reflects present curricula demands and expectations in line with professional practice. There are also contributions and comments from service users with a learning disability. This book is aimed primarily at occupational therapy undergraduate students, but will be of use to new practitioners working in the field of learning disability and other students studying topics related to learning disabilities. It meets learning needs in line with theory and practice outcomes and provides an understanding of the current issues in health and social care for people with a learning disability. It provides a basis for further learning and the depth reflects present curricula demands and expectations in line with professional practice. There are also contributions and comments from service users with a learning disability. Informative text supported by reflective activitiesReflects changes in service provision subsequent to "A Strategy for the 21st Century"Case scenarios and self assessment tasksAdvises on further readingOffers occupational therapy focus on issues that are also relevant to other health professionals.
Perspectives on occupational needs of people with learning disability / Jenni Hurst, Jane Goodman, and Christine Locke -- Historical perspectives : the lives of people with learning disabilities and the influence of occupational therapy / Jane Goodman, Jenni Hurst, and Christine Locke -- Occupations and the occupational therapy process / Jane Goodman and Christine Locke -- The interface between communication and community living / Christine Griffiths -- Occupation and health promotion / Jenni Hurst -- Activities of daily living (ADL) for individuals with a learning disability : using a sensory integrative approach / Vanessa Townsend -- Occupational choices : choosing employment? / Angela Kelsall -- Leisure / Christine Locke -- The challenges of maintaining occupation at times of transition / Jenni Hurst -- Working with parents with learning disabilities / Christine Locke -- Loss and bereavement / Jenni Hurst -- The older adult and life changes / Jenni Hurst -- More than having a say : user participation in learning disability services / Rhonwen Parry and Edwin Jones -- Working with people with learning disabilities and their networks / Sally Donati -- And finally ... a personal comment / Christine Locke, Jenni Hurst, and Jane Goodman.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Learning disabled -- Rehabilitation; Occupational therapy; Learning disabled -- Rehabilitation; Occupational therapy; Learning Disorders -- rehabilitation; Counseling -- methods; Disabled Persons -- psychology; Learning Disorders -- psychology; Occupational Therapy -- methods; Electronic books